Environmental Fate and Behavior of the Herbicide Glyphosate in Sandy Soils of Florida Under Citrus Production - Gairhe, Biwek; Liu, Wenwen; Batuman, Ozgur; Dittmar, Peter; Kadyampakeni, Davie; Kanissery, Ramdas (Frontiers in Environmental Chemistry, 2021)
Chemical weed control using herbicide glyphosate to manage emerged weeds is an important production practice in Florida citrus. Despite the extensive use of glyphosate in citrus orchards, very limited information is available on its environmental fate and behavior in Florida soils that are predominantly sandy in nature. Hence, the study's objective was to understand the adsorption-desorption, dissipation dynamics, and vertical movement or leaching of glyphosate in sandy soils in citrus orchards. Laboratory, field, and greenhouse experiments were conducted at Southwest Florida Research and Education Center in Immokalee, Florida. The adsorption-desorption behavior of glyphosate in the soils from three major citrus production areas in Florida was studied utilizing a batch equilibrium method. The dissipation of glyphosate was tracked in the field following its application at the rate of 4.20 kg ae ha-1. Soil leaching columns in greenhouse conditions were used to study the vertical movement of glyphosate. The results suggest that glyphosate has a relatively lower range of adsorption or binding (Kads = 14.28 to 30.88) in the tested soil types. The field dissipation half-life (DT50) of glyphosate from surface soil was found to be ~26 days. Glyphosate moved vertically or leached into the soil profile, up to 40 cm in the soil column, when analyzed 40 days after herbicide application. The primary degradation product of glyphosate, i.e., aminomethyl phosphonic acid (AMPA), was also detected up to the depth of 30 cm below the soil surface, indicating the presence of microbial metabolism of glyphosate in the soil.